“Your request is touching”: Marginalization, weakness, and liminality experienced by disabled graduate students in Israel - Bitman, Nomy; Yabo, Mariela (Disability Studies Quarterly, 2023)
Academic neoliberal ableism has considerable negative implications for all disabled academics, but specifically for the marginalization, liminality, and weakness of disabled graduate students. This is particularly true for the understudied and underrepresented disabled graduate students who are not native English speakers and who live in regions that are geographically and culturally distant from the English-speaking academic hegemony. This article addresses this gap by presenting a collaborative autoethnography of two disabled Israeli doctoral students. The analysis raised two themes. The first includes the complex aspects of learning to perform new academic roles – teachers, conference presenters and researchers – as disabled academics. The second includes our marginality in two contexts, namely our studied disciplines, which fail to see disability as a critical object, and the developing Israeli community of disability studies in which disabled scholars are underrepresented. On the basis of these themes, we identify four combined environments that mirror the intersection between global neoliberal ableism and the specific ableist culture found in Israel, which exacerbate our weakness, marginality, and liminality: The Israeli Disability Studies community, our discipline, the Israeli academy, and the English-speaking academy.